Seasonal sea-ice in the Arctic’s last ice area during the Early Holocene - Henrieka Detlef; Matt O’Regan; Christian Stranne; Mads Mørk Jensen; Marianne Glasius; Thomas M. Cronin; Martin Jakobsson; Christof Pearce (Communications Earth & Environment, 2023)
Marine sediment proxies for sea ice suggest that a shift to seasonal sea ice in the Lincoln Sea during the Early Holocene was related to warmer air temperatures, similar to those projected to occur under anthropogenic warming.